ACCOUNTING AND REGULATORY CHANGES IN BRAZILIAN CORPORATE LAW: AN INVESTIGATION OF THE IMPLICATIONS FOR THE REVISION OF THE TARIFF OF THE SANITATION SECTOR IN PERNAMBUCO - Cavalcanti, Luiz Arthur; Rodrigues, Raimundo Nonato; Prazeres, Rodrigo Vicente; Araújo, Juliana Gonçalves de (RC&C: Revista de Contabilidade e Controladoria, 2015)
The research aimed to highlight the implications of reconciling accounting information for regulation with the information for the corporate the process of rates revision of the sanitation sector in Pernambuco. The data collected for this study were obtained in the Financial Statements, Notes, Balance Sheets, Reports and Technical Notes of tariff revision, relating to the period of 2009/2010. Interviews were conducted and surveys were applied on the Regulatory Agency of Pernambuco and on The Company of Sanitation of Pernambuco in order to clarify the details about the accounting and regulatory process to determine and validate the selection of abnormal test results and the results obtained. These data were processed in spreadsheets, prepared with the intention of reconciling the financial statements for regulatory purposes with the information for corporate purposes. It was observed that the existing regulatory norms for the case studied did not fit to update the Brazilian corporate law, the present amendments to Law 6.404/76, the Pronouncements, Interpretations and Technical Guidance Statements. Thus, it not necessarily represent a barrier to corporate changes, lack of regulation or unsuitability or asymmetry could bring little clarity to the financial statements for regulatory purposes, and possible impacts on the values established for the review of the tariffs charged to society.